Effects of Osteoporosis Medication Use on Reprocedure Rates Following Vertebral Augmentation: A Nationwide Cohort Study - Park, Sub-Ri; Lee, Byung Ho; Suk, Kyung-Soo; Kim, Namhoo; Park, Minae; Park, Si Young; Moon, Seong-Hwan; Kim, Hak-Sun; Shin, Jae-Won; Kwon, Ji-Won (Clinics in orthopedic surgery, 2025)
Background: In this study, we aimed to investigate the effects of osteoporosis medication use and prescription duration on the rates of reprocedures for re-fractures in patients who underwent vertebral augmentation (VA). Methods: This retrospective cohort study was conducted using data collected from the National Health Insurance Service database of South Korea. Patients aged 50 years or older who underwent VA in 2012 were included in this study. A reprocedure was defined as an additional VA performed for re-fractures during a follow-up period of up to 5 years. Patients were categorized based on medication type (bisphosphonates, selective estrogen receptor modulators [SERMs], calcium supplements, or vitamin D supplements) and prescription duration (incomplete, complete, or absolute complete). The results were statistically analyzed using Cox regression and Kaplan-Meier survival analyses. Results: Among 9,070 patients included, 678 patients (7.5%) underwent reprocedures for re-fractures, with 41.0% of reprocedures performed within 6 months after VA. The reprocedure rate was higher in patients prescribed calcium or vitamin D supplements (13.3%) than in those prescribed bisphosphonates (7.7%) or SERMs (8.6%). Multivariate analysis revealed that prolonged prescription duration was associated with higher reprocedure rates, reflecting greater disease severity. The absolute complete prescription group showed a 9.07 times higher hazard ratio for reprocedure than the no-medication group. Conclusions: These findings highlight the potential of osteoporosis medication use and prescription duration as predictive factors for reprocedure rates after VA. Although patients with more severe osteoporosis require longer treatment, adherence to therapy may help reduce the risk of additional interventions over time. KCI Citation Count: 0